Modelling car motion and the calculation of the wear of wheels with the VNITsTT rolling surface profile - A. M. Orlova; Yu. V. Savushkina; V. I. Fedorova (Вестник Научно-исследовательского института железнодорожного транспорта)
The wear problem of wheels along rolling surface or thin flange is currently involved a large circle of specialists. There are opinions that it is necessary to establish new limit values for wheel wear in operation, put into practice the re-profiling (profile grin ding) of rails, install a larger number of floor-mounted lubricators in places of increased rail wear intensity, but one of the priority direction in this area is the development of a new surface rolling wheel profile for freight cars, the use of which will help to increase the turnaround time and increase the service life of the wheels in operation. Geometry of the rolling surface profile of the wheel should allow to provide a contact form between the wheel and the rail conformal or close to conformal. This solution has already found its application and achieved desired results on foreign railways (North America, South Africa, China, etc.). Authors developed a technique for designing a new wheel profile, which was used to build a profile of the rolling surface made by the Russian Research Center for Transport Technologies (LLC “VNITsTT”). As part of the study, calculations were carried out using the method of mathematical modeling of a freight car motion in the MEDYNA software package and performance indicators were evaluated on the VNITsTT rolling surface profile in comparison with the profile made according to GOST 10791 – 2011, and the wheel wear rate produced on the section of the track close to the average network operating conditions. Additionally, critical speed of the sinuous motion of the car was evaluated, which showed that despite the increased equivalent taper, the critical speed remained almost unchanged (an increase of 6 %). Theoretical calculation of the wheel resource based on the results of mathematical modeling has been made. According to the calculations, it was determined that the resource of the flange before turning for the RDCTT profile is 409.3 thousand km, and for the rolling surface — 663.3 thousand km, for the profile made according to GOST 10791 – 2011, the resource for the flange was 285.6 thousand km, and for the rolling surface 401.2 thousand km. Thus, the use of the VNITsTT profile is more effective than the profile made according to GOST 10791 – 2011 by 30.2 % for the flange and 39.5 % for the rolling surface. The developed VNITsTT profile, in comparison with the profile made by GOST 10791 – 2011, according to the results of calculations, confirmed the provision of standard indicators of the dynamic qualities of a freight car.